HEPATOZOON SPP. IN A HOARY FOX (LYCALOPEX VETULUS) FROM UBERLÂNDIA, MINAS GERAIS STATE, BRAZIL Hepatozoon spp. na raposinha-do-campo (Lycalopex vetulus) em Uberlândia (MG) - Quagliatto Santos, André Luiz; Mundim, Antonio Vicente; Castro Pereira, Heloísa; Lima de Miranda, Renata; Ribeiro de Castro, Jacqueline (Revista Acadêmica Ciência Animal, 2013)
Canine hepatozoonosis, which has been diagnosed in several regions of Brazil, can also affect wild canids. A male hoary fox (Lycalopex vetulus) was treated in August 2008 at the Center for Wildlife Studies of theVeterinary Hospital, Federal University of Uberlândia, in the municipality of Uberlândia, Minas Gerais, Brazil. After a preliminary clinical assessment, the fox was subjected to hematological and hemoparasiteexams, which revealed Hepatozoon spp. gametocytes in the blood smear. This is the first report of the presenceof Hepatozoon spp. in a hoary fox (Lycalopex vetulus) in the Triângulo Mineiro region.